Campus sweet corn to go on sale for Memorial Day weekend - Hughes, Eddie::::::::: (2013)
The Rue and Gwen Gibson Farm Market on the Fresno State campus announced that its freshly harvested campus-grown white sweet corn goes on sale Friday, May 24, just in time for Memorial Day weekend.